A Situated Comparison of Suicide and Non-Suicide Terrorist Plots and Homicides in the United States, 1990-2014. (August 2019) - Gruenewald, Jeff; Klein, Brent R.; Parkin, William S.; Freilich, Joshua D.; Chermak, Steven
This study compares suicide and non-suicide incidents in the United States by analyzing data from the U.S. Extremist Crime Database (ECDB) on terrorist incidents committed by extreme far-right (FR) and radical Islamic terrorists between 1990 and 2014. Drawing from Situational Crime Prevention (SCP), we investigate whether suicide incidents are more likely than non-suicide incidents to be directed at secure targets and to utilize firearms. Findings reveal that suicide terrorism is significantly more likely to be committed against secure targets and similarly likely to involve the use of firearms in comparison with non-suicide terrorism. In addition, suicide terrorism is more likely to be committed by lone actors, radical Islamic terrorists, and result in fatalities. Implications for terrorism prevention are discussed.